The sweetpotato community of practice celebrates science and biofortification - International Potato Center (2017)
The 7th Annual Sweetpotato for Profit and Health lnitiative (SPHI} Technical meeting aligned with the 10th Triennial African Potato Association Conference in Addis Ababa and CIP's 45th Anniversary to maximize participation. SPHI membership continues to expand. Community of Practice (CoP) participants joined in celebrating the 2016 World Food Prize recognition of Biofortification.